Novel genetic associations with five aesthetic facial traits: A genome-wide association study in the Chinese population - Wang, Peiqi; Sun, Xinghan; Miao, Qiang; Mi, Hao; Cao, Minyuan; Zhao, Shan; Wang, Yiyi; Shu, Yang; Li, Wei; Xu, Heng; Bai, Ding; Zhang, Yan (Frontiers in Genetics, 2022)
The aesthetic facial traits are closely related to life quality and strongly influenced by genetic factors, but the genetic predispositions in the Chinese population remain poorly understood. We performed genome-wide association studies (GWASs) and subsequent validations in 26,806 Chinese on five facial traits: widow’s peak, unibrow, double eyelid, earlobe attachment, and freckles. In total, 21 genetic associations were identified, of which ten were novel: GMDS-AS1 (rs4959669, P=1.29×10-49) and SPRED2 (rs13423753, P=2.99×10-14) for widow’s peak, a previously unreported trait; FARSB (rs36015125, P=1.96×10-21) for unibrow; KIF26B (rs7549180, P=2.41×10-15), CASC2 (rs79852633, P=4.78×10-11), RPGRIP1L (rs6499632, P=9.15×10-11), and PAX1 (rs147581439, P=3.07×10-8) for double eyelid; ZFHX3 (rs74030209, P=9.77×10-14) and LINC01107 (rs10211400, P=6.25×10-10) for earlobe attachment; and SPATA33 (rs35415928, P=1.08×10-8) for freckles. Functionally, seven identified SNPs tag the missense variants and six may function as expression quantitative trait loci (eQTLs). The combined polygenic effect of the associations was represented by genome-wide polygenic scores (GPSs) and contributions of the variants were evaluated using single nucleotide polymorphism (SNP) heritability. These identifications may facilitate a better understanding of the genetic basis of features in the Chinese population and hopefully inspire further genetic research on facial development.